A combined variable reluctance network-finite element VR machine modeling for stator inter-turn short-circuit diagnosis - Rabeh Chehda; Noureddine Benouzza; Azeddine Bendiabdellah; Naouel Kada Belghitri (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The work presented in this paper, proposes a comparison study between the network variable reluctance (NVR) model and the finite elements (FE) model intended for the diagnosis of stator inter-turn short-circuit (ITSC) of the variable reluctance machine (VRM). In the first place, the model of the VRM by the NRV is presented. To validate this model, the FE model of the VRM has been then studied. The detection of the ITSC is achieved by the use of the stator current spectral analysis technique. The simulation results obtained, illustrate well the interest and efficiency of the proposed model as well as of the merits of the stator current spectral analysis technique for the stator ITSC fault diagnosis of the VRM.